Genome-wide identification of the TCP gene family in Chrysanthemum lavandulifolium and its homologs expression patterns during flower development in different Chrysanthemum species - Wu, Xiaoyun; Li, Junzhuo; Wen, Xiaohui; Zhang, Qiuling; Dai, Silan (Frontiers in Plant Science, 2023)
TCP proteins, part of the transcription factors specific to plants, are recognized for their involvement in various aspects of plant growth and development. Nevertheless, a thorough investigation of TCPs in Chrysanthemum lavandulifolium, a prominent ancestral species of cultivated chrysanthemum and an excellent model material for investigating ray floret (RF) and disc floret (DF) development in Chrysanthemum, remains unexplored yet. Herein, a comprehensive study was performed to analyze the genome-wide distribution of TCPs in C. lavandulifolium. In total, 39 TCPs in C. lavandulifolium were identified, showing uneven distribution on 8 chromosomes. Phylogenetic and gene structural analyses revealed that ClTCPs were grouped into classes I and II. The class II genes were subdivided into two subclades, the CIN and CYC/TB1 subclades, with members of each clade having similar conserved motifs and gene structures. Four CIN subclade genes (ClTCP24, ClTCP25, ClTCP26, and ClTCP27) contained the potential miR319 target sites. Promoter analysis revealed that ClTCPs had numerous cis-regulatory elements associated with phytohormone responses, stress responses, and plant growth/development. The expression patterns of ClTCPs during capitulum development and in two different florets were determined using RNA-seq and qRT-PCR. The expression levels of TCPs varied in six development stages of capitula; 25 out of the 36 TCPs genes were specifically expressed in flowers. Additionally, we identified six key ClCYC2 genes, which belong to the class II TCP subclade, with markedly upregulated expression in RFs compared with DFs, and these genes exhibited similar expression patterns in the two florets of Chrysanthemum species. It is speculated that they may be responsible for RFs and DFs development. Subcellular localization and transactivation activity analyses of six candidate genes demonstrated that all of them were localized in the nucleus, while three exhibited self-activation activities. This research provided a better understanding of TCPs in C. lavandulifolium and laid a foundation for unraveling the mechanism by which important TCPs involved in the capitulum development.PCF